Perlindungan Hukum Terhadap Tata Penglolaan Air di Indonesia - Galih Puji Mulyono (University of Merdeka Malang, 2019)
This study examines the policy of legal protection of water resources in Indonesia. Legal protection of water resources is important as a rule and guidelines for human behavior as the purpose of the law to regulate public order. Legal developments regarding water resources need to be updated following the development of the community, so that the creation of legal protection for water resources can have an impact on water conservation in Indonesia. This type of legal research in writing this thesis is normative (doctrinal). The method used is a) Approach to the Law; b) Conceptual Approach; c) Comparison Approach. The results of the discussion in the form of the role of the private sector in the management of natural resources are based on the assumption of the importance of economic growth through market mechanisms in water allocation, and the importance of the role of the private sector in making investments related to the development of natural resources. England is a country famous for its prowess in the field of water management. Even the UK is a water distributor for countries that lack water such as Singapore. British water management is indeed different from Indonesia. UK water regulation uses a water privatization system.How to cite item: Mulyono, G. (2019). Perlindungan Hukum Terhadap Tata Penglolaan Air di Indonesia. Jurnal Cakrawala Hukum, 10(1), 18-29. doi:https://doi.org/10.26905/idjch.v10i1.3292